Past, present and future trends in industrial electronics standardization - Huang, V.K.L. (2018)
The Standards Group of the IEEE Industrial Electronics Society (IES) has been active in standards for industrial electronics in recent years, focusing on sensors and sensors networks, real-time industrial communications and industrial agents in the automation fields. It has also participated and collaborated with other IEEE societies such as the Instrumentation and Measurement Society (IMS) in the IEEE 1451 sensor networks standards family, and with government entities such as the US National Institute of Standards and Technology (NIST). This paper gives a brief synopsis of IES standards activities and the trends it sees in industrial electronics standardization in the coming emerging technologies such as Internet of Things (IoT)/Industrial IoT (IIoT), 5G communications, industrial wireless and possibly transportation electrification. All these technologies are expected to be disruptive to the industry in the coming years and standards must be generated to be effective and beneficial to industry and society. The IES Standards Group anticipates more contributions to the IEEE 1451 standards family, industrial agents, industrial wireless applications with NIST, and possibly with standards activities within Industry 4.0 in the coming years.